Estudos in vitro e in vivo da atividade da neolignana licarina a livre ou associada ao ácido ascórbico sobre leishmania (leishmania) amazonensis sensível e resistente ao antimonial trivalente - Andrade, Patrícia Néris (2017)
The drugs available for the treatment of leishmaniasis are usually very toxic. In Brazil, the treatment of these diseases is mainly performed by parenteral administration of pentavalent antimony Glucantime®,!used as the first choice drug.! However, therapy with this drug is associated with serious side effects and often presents failure due to the selection of Leishmania sp. resistant to antimonials. Therefore, researches aiming the search for bioactive molecules that are effective against the parasites, without significant toxicity to humans, are necessary. In this context, this work aimed to evaluate the antileishmanial activity of the neolignan Licarin A in experimental models in vitro and in vivo. Licarin A showed in vitro antileishmanial activity on promastigotes (IC50 of 22.13 μg/mL), axenic amastigotes (EC50 of 10.78 μg/mL) and intracellular amastigotes (EC50/72h of 5.68 μg/mL) forms of Leishmania (L.) amazonensis. Its action on infected macrophages was associated with immunolodulatory activity by increasing the levels of interleukin (IL)-12 and nitric oxide (NO) in 15.2% (p ≤ 0.05) and 120.34% (p ≤ 0.05), respectively, and reduction in the level of IL-6 and IL-10 in 51.5% (p ≤ 0.05) and 42.78% (p ≤ 0.05), respectively, after treatment with the concentration of 15 μg/mL of Licarin A for 72h. It was found that licarin A was also effective on parasites of L. (L.) amazonensis resistant to trivalent antimony (SbIII). Although these antimony resistant parasites showed more virulence than the corresponding sensitive culture, in both in vitro and in vivo infection models, licarin A was equally effective against both strains. It was also observed that Swiss mice infected with L. (L.) amazonensis and treated with licarin A and ascorbic acid had significant reduction of 40.78% (p ≤ 0.05) in lesion size from the fourth week of treatment, as well as! reduction in the parasitic load on the lymph node and spleen of these animals. In addition, paw histoarchitecture of treated animals was partially restored by reorganization of collagen fibers, reduction of edema and cell infiltrate in the dermis, hypodermis and between the muscle fibers. This result was also associated with an immunomodulatory response, due to an increase in interferon (IF)-γ production of 266.7% (p ≤ 0.001) by the lymph node cells of treated animals.! The co-treatment with licarin A and ascorbic acid had no significant toxicity, since the animals did not present alteration in the weight, coat or in biochemical and hematological parameters analyzed. Thus, it can be concluded that licarin A has expressive antileishmanial activity in the murine model, being a promising molecule to be better investigated in the search for new treatments for leishmaniasis.